Health care to immigrant and Portuguese pregnant women in Portugal - Emília de Carvalho Coutinho; Alcione Leite da Silva; Carlos Manuel Figueiredo Pereira Pereira; Alexandra Isabel Almeida; Paula Alexandra Batista Nelas; Vitória Barros Castro Parreira; Maria Odete Amaral (SciELO, 2014)
This study aimed to assess the care received and the barriers faced by immigrants and Portuguese pregnant women in Portugal. This is an exploratory qualitative study, resorting to applying semi-structured interviews to 60 immigrant and 22 Portuguese women. Content analysis supported by QSR Nvivo10 program was used. The study was approved by an Ethics Committee. The results showed four categories related to affective dimensions-relational, cognitive, technical-instrumental and health care policy for pregnant women. As for the barriers in health care, these were mentioned by some of the expectant mothers, especially immigrant women. Almost all, both immigrant and Portuguese, pregnant women were satisfied with the health care.